If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = y + 9 Reorder the terms: 5 = 9 + y Solving 5 = 9 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 5 + -1y = 9 + y + -1y Combine like terms: y + -1y = 0 5 + -1y = 9 + 0 5 + -1y = 9 Add '-5' to each side of the equation. 5 + -5 + -1y = 9 + -5 Combine like terms: 5 + -5 = 0 0 + -1y = 9 + -5 -1y = 9 + -5 Combine like terms: 9 + -5 = 4 -1y = 4 Divide each side by '-1'. y = -4 Simplifying y = -4
| -30=-5/3(x=25) | | m/-4=5=14 | | -7r+6=-15 | | 5x-18=6x+8 | | f(x)=6x^3-53x^2-11x+2 | | .35y=15 | | 5x^2-lnx=0 | | -10-7m=-6m | | 3k+4=5k-10 | | 10+7p=24 | | 18x-8=13x-33 | | 2x-6+21=-3 | | -b-10=10+10+9b | | 4x-84=72-9x | | 4(2x+9)=-46+10 | | 2(x-3)-5(x-1)=4 | | -2x-5y=12forY | | b-10=10+10+9b | | 3(5x+6)-2(3-4x)=-11 | | 5z+14=7z-30 | | 4n^2-12n-320=0 | | x*x-100=0 | | 10-d=d-8 | | 340=x*490 | | 5(3t-4)-6=12t+4 | | -3r+6=r-6 | | 10-3y=6 | | 8u=7u+1 | | 18-13=1/2a=3/4a-5/8a | | 2z/7-2=7 | | 8y+4-6y=8+y+1 | | -8y-20=5y-20 |